2020
DOI: 10.1109/access.2020.2984548
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and Performance Evaluation of Hybrid Beamforming for 5G and Beyond Systems

Abstract: Increasing demand for higher data-rate wireless connectivity with lower latency is fueling the explorations of millimeter-wave (mmWave) spectrum and massive MIMO communications. Both technologies are recognized as the key enablers of 5G and beyond 5G (B5G) networks. Hybrid beamforming is one of the most promising energy and cost-effective approaches to realize mmWave massive MIMO communications with lower complexity and smaller training overhead. With the motivation of giving more insights and in-deep technica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 133 publications
(213 reference statements)
0
19
0
Order By: Relevance
“…In [65], a hybrid precoding scheme based on equal gain transmission and the ZF has been proposed to reduce the hardware cost and processing complexity of massive MIMO systems. Detailed explanations of hybrid precoding with hardware architectures and methods of deployment with the impact of CSI have been comprehensively discussed in [66]. It was shown that the hybrid beamforming has a critical impact in minimizing the hardware cost since a small number RF chains at the transceivers was utilized.…”
Section: Signal Processing Challengesmentioning
confidence: 99%
“…In [65], a hybrid precoding scheme based on equal gain transmission and the ZF has been proposed to reduce the hardware cost and processing complexity of massive MIMO systems. Detailed explanations of hybrid precoding with hardware architectures and methods of deployment with the impact of CSI have been comprehensively discussed in [66]. It was shown that the hybrid beamforming has a critical impact in minimizing the hardware cost since a small number RF chains at the transceivers was utilized.…”
Section: Signal Processing Challengesmentioning
confidence: 99%
“…In this article, our contributions are as follows: Recent literature studies [3], [36], [37] have discussed multi-beam antennas based on beamforming circuits, optical components, and different phase switching methods, in general. Although, they failed to discuss in detail the different types of beamforming circuits based on the BM number of layers.…”
Section: B Contributions and Organization Of This Articlementioning
confidence: 99%
“…The RSS of the l th path is P l = P t +G t +G r −L [36], where P t is the transmit power, G t is the transmit antenna gain, G r is the receive antenna gain, L is the path loss obtained by (5) for the LoS path and by ( 5) and ( 7) for the single-reflection path. For the non-existent path, P l = −∞.…”
Section: ) Path Representationmentioning
confidence: 99%
“…Massive multi-input multi-output (mMIMO) systems with an extremely large number of antenna elements can significantly improve the spectral and energy efficiency in millimeter-wave (mmWave) frequencies via focusing narrow and high-gain beams towards a small region and thus increase the overall data rate and channel capacity via spatial multiplexing [2]. For downlink transmission, multi-user mMIMO (MU-mMIMO) using hybrid precoding (HP) is prevalently deployed at the BS to tackle above-mentioned challenges, where HP supports a large number of antenna elements via a concatenation of a radio frequency (RF) beamformer, few power-hungry RF chains and a low-dimension baseband precoder [3]- [5].…”
Section: Introductionmentioning
confidence: 99%